2002
DOI: 10.1002/j.2161-1920.2002.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving congruence between employee interests and county jobs: a win‐win proposition

Abstract: Assisting employees to explore internal job switches rather than leaving an organization is a positive measure aimed at enhancing employee retention and job satisfaction. This article describes how a municipal county government used J. L. Holland's (1 992) occupational classification system to help employees achieve congruence between their interests and their job requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…(1998) reported that transition activities in which students with disabilities could explore and match their interests (e .g ., job tryouts, job shadows, internships) led to successful job entry . Furthermore, Beale and Holinsworth (2002) indicated that individuals whose jobs did not match their interests demonstrated low job production, job dissatisfaction, and personal distress . The match between career interests and employment opportunities has been described by many career theories as a significant factor in career planning stages (Holland, 1997;Super, 1994) .…”
Section: Transition Outcomes and Interest-job Matchmentioning
confidence: 99%
See 1 more Smart Citation
“…(1998) reported that transition activities in which students with disabilities could explore and match their interests (e .g ., job tryouts, job shadows, internships) led to successful job entry . Furthermore, Beale and Holinsworth (2002) indicated that individuals whose jobs did not match their interests demonstrated low job production, job dissatisfaction, and personal distress . The match between career interests and employment opportunities has been described by many career theories as a significant factor in career planning stages (Holland, 1997;Super, 1994) .…”
Section: Transition Outcomes and Interest-job Matchmentioning
confidence: 99%
“…The match between career interests and employment opportunities has been described by many career theories as a significant factor in career planning stages (Holland, 1997;Super, 1994) . This interest-job match, or congruence, has been studied in relation to career maturity (Ohler & Levinson, 1996), aspects of wellbeing (Meir, Melamed, & Dinur, 1995), and person-environment match (Thompson, Flynn, & Griffith, 1994) and has been used to explore employee and job retention in community employment programs (Beale & Holinsworth, 2002) .…”
Section: Transition Outcomes and Interest-job Matchmentioning
confidence: 99%
“…Lambert, Hogan and Barton 34 used turnover as a dependent variable in a study of the impact of job satisfaction on turnover. If we assume clerks are not likely to leave for the reasons presented above, as well as based on their long tenure, we may find a connection between low turnover and plateauing, as in the study of Beale and Holinsworth 35 who looked at the addition of responsibilities that occurred without an official "promotion." However, for our purposes we anticipate no association between opportunities for promotion/advancement and overall job satisfaction.…”
Section: Hypothesesmentioning
confidence: 99%